A new species of Pseudocrenilabrus (Perciformes: Cichlidae) from Lake Mweru in the Upper Congo River System - Katongo, Cyprian; Seehausen, Ole; Snoeks, Jos (Zootaxa, 2017)
Pseudocrenilabrus pyrrhocaudalis sp. nov. is described from Lake Mweru in the upper Congo River drainage, on the border of the Democratic Republic of Congo and Zambia. This species, which appears to be endemic to the lake, lives in sympatry with P. philander. Pseudocrenilabrus pyrrhocaudalis sp. nov. is distinguished from P. philander in nuptial males by the presence of an orange colour on the ventral part of the body and the proximal parts of the anal and caudal fins, a broad band of bright white on the distal edge of anal and caudal fins, a uniform grey head and dorsum, and a subtruncate caudal fin. In addition, P. pyrrhocaudalis has a shorter snout, a narrower head, a smaller interorbital distance, a smaller pre-anal distance, a more slender caudal peduncle and fewer scales around the caudal peduncle in both sexes.